An evaluative study on internet banking security perceptions and practices among bank customers in Ahmedabad city - Jheel Rathod; Devam Vaishnav; Jignesh Vidani (Journal of Advanced Research in Accounting and Finance Management, 2024)
In this generation of computers, Internet banking is the most common word for everyone. Now, we can easily transfer money to anyone, anytime, and everywhere. Banks have already taken important steps for this around the world. Most of the people in India run their livelihoods in agriculture, farming, small industries, and driving. However, there are much more factors in Gujarat, in which some areas seem to have reduced its usage. In this paper, we are trying to analyze the factors that are affecting the use of E-banking systems in Ahmedabad and to summarize and analyze customers’s perceptions of Internet banking systems. The purpose of the paper is to uncover the customers’ satisfaction with Internet banking services and evaluate their level of satisfaction with e-banking. The purpose of this paper is to find out how customers perceive Internet banking services and how satisfied they are with e-banking. The paper presents the analysis of 30 Internet banking customers who have bank accounts with different banks in Ahmedabad city. The basic features that affect the usage of Internet banking services are studied, and based on that, some possible suggestions are provided in the research paper.